Profitabilitas, Leverage dan Penghindaran Pajak - Wuriti, Ni Made; Noviari, Naniek (E-Jurnal Akuntansi, 2023)
Tax avoidance is an activity to legally minimize tax payments but is not wanted by the government because it can lead to reduced state revenues. This research aims to obtain empirical evidence regarding the influence of profitability and leverage on tax avoidance. The theory used is the Theory of Planned Behavior (TPB). The population in this study are all mining companies listed on the IDX for the 2017-2021 period. The sampling technique used a purposive sampling method with a total of 60 samples obtained. The analysis technique used is multiple linear regression analysis. The results of this study indicate that profitability has a positive and significant effect on tax evasion, while leverage has no effect on tax evasion. The theoretical implications of this research are able to confirm the TPB based on the results of the tests that have been carried out. The practical implications of this research can provide knowledge that can be used as consideration for investors and the government. Keywords: Profitability; Leverage; Tax Avoidance